Efektivitas Minyak Atsiri Daun Cengkeh (Syzygium aromaticum) dan Biji Pala (Myristica fragrans) terhadap Low Back Pain: Studi Perbandingan di Kota Ambon - Lameky, Vernando Yanry; Akollo, Isak Roberth; Tiwery, Rosdiana Tisye (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Low back pain is a global health problem that affects quality of life and work productivity. The causes vary, from injuries to degenerative diseases. One alternative approach to relieve LBP is clove leaves and nutmeg. Clove leaves contain eugenol, which has anti-inflammatory, analgesic, and muscle relaxant properties, while nutmeg contains myristicin and essential oils that effectively relieve pain. The combination of the two, which can be used in the form of massage oil or herbal ointment, has the potential to provide a synergistic effect in reducing pain and inflammation. This study aims to analyze the effectiveness of clove leaf and nutmeg essential oils in reducing LBP pain in Ambon City. The research method used was quasi-experimental with a pretest-posttest design involving 50 respondents who experienced LBP and were divided into two groups. Data were collected using a numeric pain assessment scale and analyzed using the Paired Sample T-Test. The results showed that 64% of respondents in the clove leaf oil group and 76% in the nutmeg seed oil group experienced moderate pain before the intervention. After the intervention, a significant decrease in pain was found, where the clove leaf group showed an average decrease in pain from 2.36 to 0.24 (p = 0.000), while the nutmeg group from 2.24 to 1.48 (p = 0.001). This study indicates that clove leaf essential oil is more effective in relieving LBP pain than nutmeg seed oil. These findings provide recommendations for using local natural resources as an alternative non-pharmacological therapy in managing LBP.